In vitro anticancer, antioxidant and chelating activities of natural organosulfur compounds originated from Türkiye: an investigation on breast and colorectal cancer cells - Polat Korkunc, Ummugulsum; Calik, Hilal; Kose, Leyla P. O. L. A. T.; Cakir Koc, Rabia; Karakuls, Emine (Tubitak Scientific & Technological Research Council Turkey, 2025)
Background/aim: Ta & scedil;k & ouml;pr & uuml; garlic, cultivated in the Ta & scedil;k & ouml;pr & uuml; region of Kastamonu Province, is highly renowned in T & uuml;rkiye. This study aimed to determine the anticancer and antioxidant effects of extracts from Kastamonu Ta & scedil;k & ouml;pr & uuml; garlic on human breast cancer and colorectal cancer cells. Materials and methods: Ta & scedil;k & ouml;pr & uuml; garlic, which contains natural organosulfur compounds (OSCs), has a geographical registration. Garlic contains oil- and water-soluble OSCs known to exhibit anticancer activity by interfering with MCF-7 and Caco-2 proliferation and tumor metastasis. This study assessed the antiproliferative activity of oil- and water-soluble garlic extracts with and without glutathione at different concentrations using the XTT assay on NIH/3T3, MCF-7, and Caco-2 cell lines over 24 h. In addition, the reducing capacity, radical scavenging activity, and metal chelation activity of OSCs in Ta & scedil;k & ouml;pr & uuml; garlic were analyzed. Results: Both oil- and water-soluble garlic extracts significantly inhibited the proliferation of MCF-7 and Caco-2 in a dose-dependent manner after 24 h of incubation. The half-maximal inhibition concentration (IC50) values of OSCs and positive controls for N,Ndimethyl-p-phenylenediamine cation (DMPD.+) radical removal and 2,2'-bipyridyl-Fe2+ chelation activity were 129.593-1004.346 and 165.065-495.195 mu g/mL, respectively. Furthermore, the reducing impact of OSCs and positive controls were evaluated based on their cupric ion (Cu2+) reducing capabilities. All results were compared with the respective positive controls. Conclusion: The findings revealed that oil-soluble garlic extracts exhibited anticancer properties against both Caco-2 and MCF-7 cancer cells, without inducing any cytotoxicity in non-cancerous NIH/3T3. In addition, water-soluble extracts have higher antiproliferative activity on Caco-2 and MCF-7 cells in a dose-dependent manner compared to oil-soluble extracts. However, they also exhibited notable cytotoxicity on fibroblast cells. OSCs showed limited activity in reduction and radical scavenging assays but demonstrated strong chelating activity. These results suggest that both water-soluble and oil-soluble garlic extracts hold promising anticancer potential against both MCF-7 and Caco-2.
Keywords: Kastamonu Ta & scedil; k & ouml; pr & uuml; garlic; organosulfur compounds; cell viability; breast cancer; colorectal cancer; antioxidant activity; metal chelating capacity; GLUTATHIONE; CAPACITY; General & Internal Medicine